TATA KELOLA TI UNTUK MENINGKATKAN MUTU MANAJEMEN RUMAH SAKIT PRATIWI IBU DAN ANAK TANGERANG - Noer Azni Septiani (Paradigma, 2013)
In the IT governance process to improve the quality of hospital management Pratiwi TangerangMother and Child, authors use the framework Enterprise Architecture Planning by Steven H.Spewak. Thinking concept of strategic planning / IT from Steven H. The method of enterprisearchitecture Spewak Plan (EAP) departed from the SI and IT investment conditions in the past thatcan not provide benefits to the organization's business objectives, capture business opportunities,and the growing phenomenon of organizational competitive advantage of being able to harnessthe potential of SI and TI. The situation can occur due to SI and IT strategic plans that focus lesson business, do not understand that part of the business opportunities, and just to make a strategyfor technology needs alone. Hence Steven H. Spewak make strategic planning framework of IS / ITwith the method of enterprise architecture methods Plan (EAP) is to divide into 4 stages, 1.Planning Initiation, 2. Business Modelling and Current Technology, 3. Data Architecture,Application Architecture and Technology Architecture, 4. Implementation. The results of thisresearch proposal is a strategic planning framework for Information Systems / InformationTechnology that can be used in Hospitals Pratiwi Mother and Child Tangerang.Keywords: Strategic Planning of Information Systems / Information Technology, EAP, Methodology SI / IT